ANALISA 7P MARKETING MIX UNTUK PENGEMBANGAN STRATEGI MANAJEMEN PEMASARAN PADA PERUMAHAN GRAND SUTAWANGI MAJALENGKA - IKA KARTIKA (Jurnal Ilmu Ekonomi dan Bisnis, 2022)
Housing is currently a commodity that is highly sought after by young couples because it is supported by subsidized mortgage facilities with fairly low interested rates. To increase the number of sales required a good marketing strategy. The marketing management strategy with the 7p concept is very effective in increasing sales turnover. The purpose of this research activity is as an effort to improve the quality of Grand Sutawangi housing management through the preparation of an accurate business strategy in order to develop the Grand Sutawangi Housing business. The analytical tool used is the marketing mix method. This study uses a descriptive qualitative research method. From the research results obtained, marketers should expand their marketing reach. Not only offering it to factory employees and market traders, but also offering it to banking employees, civil servants, or other companies to increase sales turnover. In addition, the company should increase the number of employees, especially in the marketing department so that sales turnover will increase.